Patterns in Microservices-based Development: A Grey Literature Review - Rocha, Fabio Gomes; Soares, Michel S.; Rodriguez, Guillermo (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2023)
Microservices emerged due to the massive adoption of cloud computing and the need to integrate legacy systems. However, there still needs to be a greater understanding of adopting a microservice-based architectural style. Besides, there is a need for guidelines to operationalize those microservices. We conducted a grey literature review to identify commonly used architectural patterns and how they are implemented following design patterns. We present two key contributions. Firstly, we identified four architectural patterns and 23 design patterns. Secondly, we identified a catalog of tools for implementing the main patterns adopted when using the microservices style. The Proxy and the SAGA patterns are the most used in communicating and linking data for services. Additionally, tools such as Kubernetes, Docker, and Amazon WS are the most used for implementing microservices and deploying them into containers.